(3edLC GdNGFajf aj JQLeI SjOj CHj GdQLGd hSjOj LfOd Hefjfs - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s
(3ChdgG (B:s
(3hHYO, agPG JYdjb SejJg edLC GdNGFajf SCdfi aj JYdjbg TjNfG GdUGdM Rjf GdOjf YHOGdQMef Hf EHQGgje GdPfGHi GdUGdMj GdMfHdj s
(3BNQgG (B:s
(3hGSJeQ Ydi bOeg hWQjbg Edi Cf eGJ HbQjI efjf ai QeVGf SfI SHY hNeSjf hSJeGFI s
(3GfXQ HQbe (B511 (3JGQjNs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B291s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B416 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs